2022
DOI: 10.1155/2022/2438612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Method of Psychological Intervention Combined with Health Education on Lung Cancer Patients Undergoing Chemotherapy

Abstract: At present, lung cancer has become clinically the malignant tumor with the highest incidence and mortality rate in China. Smoking, environmental pollution, infection, etc., are closely related to lung cancer. To investigate the effect of the nursing method of psychological intervention combined with health education on lung cancer patients undergoing chemotherapy, 70 lung cancer patients who received chemotherapy in our hospital from June 2017 to June 2020 were selected and randomly divided into a routine inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Therefore, how to reduce or alleviate the side effects of chemotherapy and enhance the QOL of patients has become an urgent problem to be solved. With the insufficient understanding of the disease, LC patients are often accompanied by serious negative emotions such as annoyance, fear and depression with the clinical manifestations of distress, reduced self-esteem and crying once they are informed of the disease (19). While seriously disturbing the clinical treatment, these negative emotions also affect the sleep and QOL of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how to reduce or alleviate the side effects of chemotherapy and enhance the QOL of patients has become an urgent problem to be solved. With the insufficient understanding of the disease, LC patients are often accompanied by serious negative emotions such as annoyance, fear and depression with the clinical manifestations of distress, reduced self-esteem and crying once they are informed of the disease (19). While seriously disturbing the clinical treatment, these negative emotions also affect the sleep and QOL of patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that psychological nursing procedure for patients undergoing radical resection of lung cancer can reduce SAS and SDS scores. The psychological nursing procedure is aimed at the role of the patient, and applies the biological-psychological-social medical model to the treatment process of patients, so as to improve the patient’s psychological condition and optimize the patient’s self-emotional management ability ( 15 ). This method assesses the patient’s psychological status, master the causes of unhealthy psychology and formulate corresponding psychological intervention programs, which can help patients reduce negative psychology, alleviate the pain caused by the tumor itself and treatment, and help patients face difficulties positively ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, patients were briefed on pain and pharmacological remission and were told to follow the doctor's advice to take analgesics. The pain threshold of patients was also raised through distraction when they were in pain (7) Posture nursing: the medical staff gave patients guidance on postures and appropriately assisted patients to be in a comfortable position to avoid pressure ulcers (8) Exercise and diet care: patients were given scientific and appropriate exercise guidance based on their personal information and condition, so as to help them improve immunity and accelerate recovery.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Chemotherapy, a common treatment for patients with advanced LC, may also lead to adverse emotions such as irritability, depression, and cancer-related fatigue [ 4 , 5 ], all of which will not only exert varying degrees of negative effects on the self-efficacy and life quality of LC patients undergoing chemotherapy but also reduce patients' treatment compliance that lowers their treatment compliance [ 6 , 7 ]. This puts forward a demand for the management optimization of patients with LC chemotherapy, and exploring an effective and reliable high-quality nursing model is of positive significance for the rehabilitation of such patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%